Analysis of Community Participation in the Development of Riangsunge Beach as a Tourist Attraction in Ritaebang Village, East Flores Regency - Damianus Sonny Lamoren; I Wayan Adi Putra Ariawan; Imelda Regina Pellokila; Leonardyah Boso Wulon (International Journal of Green Tourism Research and Applications, 2025)
Riangsunge Beach a tourist destination in East Flores Regency, has been developing and developing in recent years. The development and development were carried out significantly by the Regional Government through the Tourism Office. This research is motivated by the minimal involvement of the community in the development of Riangsunge Beach as a tourist attraction in Ritaebang Village, West Solor District, East Flores Regency. This study aims to examine the participation of the local community in the development of tourism in Riangsunge Beach. This study uses a qualitative descriptive approach. Data were obtained through in-depth interviews, surveys, and observations. The informants in this study were the former head of the TANPAR Pokdarwis, Pokdarwis members (2 people), 1 new manager, and 2 community leaders. The data obtained is then analyzed rationally based on certain logical thinking patterns. The results of the study show: 1). Community participation in the planning stage is very minimal; 2). Not involving the entire community in the implementation stage; 3). Community participation in decision-making is still very minimal; but 4). Community participation in the evaluation stage is considered quite high. Overall, in the tourism development process, the role of the government in this case the Government tourism office is still very dominant.